Causal factors affecting the development of community product standards for the new generation of agricultural network in 7 upper southern provinces - Audnoon, Patchayamas; Suakaew, Utid; Manassong, Chonlada; Suwannarin, Patcharee; Thepjaroen, Arunee (Journal of Rattana Bundit University, 2020)
The objective of this study is to 1) study the level of standardization of community products for the new generation of agricultural network in 7 provinces in the upper southern region, 2) to study the causal factors affecting the development of standard of the new generation of agricultural network community products in 7 upper southern provinces. 3) to create a models for the development of community product standards for the new agricultural network in 7 upper southern provinces. The study was conducted with a sample of 374 people by random sampling. Use questionnaires as tools for data collection Statistics used in data analysis including confirmatory element analysis at the statistical significance level 0.05. The results of the research showed that the development of standardized product for the new generation of agricultural network communities in 7 upper southern provinces Comes from management factors coupled with product differentiation factors Index of standard development of new agricultural community products is better than Bring only one management factor into operation for development. The structural equations that are consistent with the empirical data also show the sub-factors that are supporting factors for the development of community product standards for the new generation of agricultural network in 7 provinces in the upper southern region.